The Empirical Studies of China's Enterprise Bankruptcy Law: Problems and Improvements†. Issue 1 (19th April 2018) - Lin, Shaowei
Abstract: Over the past 9 years since the implementation of China's Enterprise Bankruptcy Law in 2007, it has contributed to some measures of regulating market practice and rearrangement of market resources and has become an integral part in an improved legal system of China's market economy. However, a closer look at the effect of implementing the Enterprise Bankruptcy Law shows that the number of bankruptcy cases after its implementation, instead of increasing, has taken on a trend of decreasing. Even under the influence of the 2008 financial crisis, no significant increase in the number of Chinese bankrupt enterprises means that China's Bankruptcy Law failed to play its due role, leaving a large gap as desired. As such, this article aims to examine the problems arising from the implementation of the Bankruptcy Law and, taking this as guidance, probe into the reasons hidden behind and propose possible improvement measures. It is expected that the Bankruptcy Law would increasingly play a key role in the development of China's market economy, particularly under the current situation where Chinese government proposes to clean up zombie businesses. Copyright © 2018 INSOL International and John Wiley & Sons, Ltd.